The impact of working from home on support staff members of the University of Free State at the QwaQwa Campus - Mogotsi, Naledi Rethabile (University of the Free State, 2022)
The University of the Free State, QwaQwa, never had to experience working from home (WFH) before the world was faced with the Covid-19 pandemic. The purpose of this study was to explore the different perceptions and experiences of the WFH era among the support staff. In a nutshell, the study aimed to investigate how employees at the UFS QwaQwa were affected psychologically, emotionally, and financially whilst working from home during the lockdown period. The reason for selecting UFS QwaQwa was because of the different geographical dynamics, as the challenges experienced in QwaQwa differ from its co-campuses in Bloemfontein. Using the qualitative method, the researcher conducted semi-structured, open-ended questions thus one could obtain a broader range of responses. The method used allowed the researcher to examine the primary objective of the research to acquire more insight into the impact of WFH on the support staff. The results showed that the participants went through different dynamics of making WFH work, despite the circumstances they faced, whether it would be distractions by the children, electricity, or the environment the participants stayed in. There were also many positive outcomes of WFH; many participants benefited financially by not having to travel to work and by spending more time with their families. It was evident in the findings that this study will be a great way for the institution to be more informed of what the support staff experienced, and it gave more clarity on what the impact of WFH was on support staff. The study is a valuable contribution towards enhanced staff well-being and the flexible working policy enhancement in future, not only for the UFS, but even for other institutions at large.
Dissertation (MBA (Business Administration))--University of the Free State, 2022